Relationships among climatological vertical moisture structure, column water vapor, and precipitation over the central Amazon in observations and CMIP5 models. Issue 4 (18th February 2017) - Lintner, Benjamin R.; Adams, David K.; Schiro, Kathleen A.; Stansfield, Alyssa M.; Amorim Rocha, Alciélio A.; Neelin, J. David
Abstract: Bias and spread in Coupled Model Intercomparison Project Phase 5 simulated vertical specific humidity ( q ) structure are examined and related to both precipitation and column water vapor (cwv) near Manaus, Brazil, site of the recent Green Ocean Amazon campaign. Simulated seasonal mean q profiles are typically too dry, especially at low levels and during the local dry season, consistent with previously identified surface hydroclimate biases in the Amazon. Multimodel empirical orthogonal function analysis of the models' monthly climatological q profiles indicates two significant modes of ensemble spread in moisture vertical structure, with the leading mode peaked at low levels and the second mode in the lower free troposphere (LFT). While both modes project onto simulated cwv spread, only the first projects on precipitation, suggesting inconsistent sensitivity of simulated rainfall to LFT moisture. Relative to observations, models with high cwv and low‐level moisture errors tend to exhibit high precipitation error. Key Points: CMIP5 vertical moisture profiles in the Amazon are too dry compared to observations at low levels, especially during the dry season Two modes capture spread in vertical moisture structure, with one mode peaked at low levels and the other in the lower free troposphere Comparing these modes to rainfall spread points to inconsistent sensitivity of CMIP5‐simulated rainfall to vertical moisture structure